Alternate gas washout indices: Assessment of ventilation inhomogeneity in mild to moderate pediatric cystic fibrosis lung disease. Issue 11 (30th August 2018) - Nyilas, Sylvia; Bigler, Anja; Yammine, Sophie; Kieninger, Elisabeth; Rochat, Isabelle; Ramsey, Kathryn; Casaulta, Carmen; Moeller, Alexander; Latzin, Philipp; Singer, Florian
Abstract: Introduction: Normalized phase III slope (SnIII ) indices from multiple breath washout (MBW) estimate ventilation inhomogeneity. Alternate (*) protocols for SnIII indices exist, however the utility of these outcomes in children with mild‐to‐moderate cystic fibrosis (CF) is unknown. Methods: We measured nitrogen MBW and spirometry in 135 children (43 controls) aged 4‐18 years. We assessed validity, practicability, and reliability of SnIII protocols. Outcomes included the ability to detect abnormal lung function, test agreement, measurement duration, intra‐test repeatability, and quality. Results: Lung clearance index (LCI) was abnormal in 80 (87%), Scond in 55 (60%), Scond* in 17 (19%), Sacin in 10 (11%), Sacin* in 11 (12%), and FEV1 in 28 (30%). Alternate protocols reduced measurement duration. Agreement of indices to detect abnormal lung function was poor. The quality of analysis and repeatability deteriorated with the alternate technique compared to standard. Conclusion: In children with mild‐to‐moderate CF lung disease, alternate protocols seem practical but clinimetric properties of standard SnIII protocols are preferable.